A Bibliometric Analysis of the Development of Research on Social and Economic Inequality in Developing Countries - Jan Horas Veryady Purba; Loso Judijanto; Dyah Ayu Dwi Kusumaningrum; Ibadurrahman Ibadurrahman (West Science Social and Humanities Studies, 2023)
This bibliometric analysis explores the landscape of research on social and economic inequality in developing countries, employing a comprehensive approach that integrates co-authorship networks, keyword co-occurrence patterns, journal mapping, and geographical distribution maps. The study draws on a vast repository of scholarly publications, shedding light on key themes, influential authors, and global research trends. Co-authorship networks reveal collaborative patterns, emphasizing the importance of interdisciplinary approaches in understanding inequality. Keyword co-occurrence patterns identify central themes, highlighting the multifaceted dimensions of social and economic disparities. Journal mapping showcases pivotal platforms shaping the discourse, aiding researchers in navigating the academic landscape. Geographical distribution maps unveil regional concentrations and gaps, prompting nuanced explorations of inequality within specific contexts. The synthesis of these results provides a comprehensive understanding of the field, guiding future research endeavors and informing evidence-based policy interventions for inclusive development.